The US Recognition of Jerusalem: Aspects and Implications - Shahzad Hussain (Research Parks Publishers, 2021)
The status of Jerusalem lies at the heart of Palestine-Israel conundrum. Its disputed status is pelagus forsit for the resolution of the intractable Palestine conflict. The Palestinians have always regarded Eastern Jerusalem as capital of their future state under Two-nation solution. On the other side, Israel declared in 1998 to further expand Jerusalem by annexing the surrounding areas as well. This paper investigates the Trump administration’s stance on relocating the US embassy from Tel Aviv to Jerusalem, its implications for Palestinian state and broad reactions of the world community.